Isolation and Molecular Identification of Fungal Contamination on the Eggshells of Lepidochelys olivacea L. Collected from Coastal Waters - Ni Made Wagi Ambakesari; Putu Angga Wiradana; I Gede Widhiantara; I Wayan Rosiana; Muhammad Khaliim Jati Kusala (Journal of Applied Veterinary Science And Technology, 2024)
Background: One of the causes of the decline in the Olive ridley turtle population is the low egg hatching rate due to contamination by pathogenic fungi. Purpose: This study aims to evaluate the results of the isolation and molecular identification of fungal contamination on the eggshells of olive ridley turtles that failed to hatch from three coastal waters in Bali province. Method:  Sampling was done using the purposive sampling technique. Samples of failed hatching eggshells from the coast were collected, as many as 2 eggs/semi-natural nest at TCEC. Samples were cultured on PDA media. Macroscopic and molecular identification methods were carried out to determine the species level of fungal isolates. Results:  The results showed that 10 fungal isolates were successfully collected. Isolates KL1 and SG1 had white colony surface characteristics, isolates KL4, SY2 and SY3 showed black colonies, and isolates KL2, KL3, SG2, SG3, SY4 had green colonies. Three similar isolates were sent for further molecular identification. The BLASTn results of the nucleotide sequences of isolates SY2 and SG3 showed a similarity to Aspergillus niger strain PHY105 (91%), while fungal isolate KL1 had a similarity to Fusarium solani strain 87, by 98%. Conclusion:  This study provides new information about the pathogenic fungi, Fusarium solani strain 87 and Aspergillus niger strain PHY105, which are suspected to be the cause of the hatching failure of olive ridley turtle eggs.